The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s0100-83582015000400002
|View full text |Cite
|
Sign up to set email alerts
|

Correlación Espacial Entre Malas Hierbas en Una Pradera Y Su Relación Con La Conductividad Eléctrica Aparente Del Suelo (Ce a )

Abstract: -Keywords: geostatistics, soil and biological attributes, spatial variability, soil management, grassland management. INTRODUCCIÓNEn los países europeos es una práctica habitual el pastoreo en praderas cultivadas, o también, el uso de praderas para la producción de forraje de diferentes tipos. En este sentido, es necesario comprender la dinámica y la ecología de los agrosistemas de producción, para poder determinar cuáles son las mejores alternativas de manejo para el suelo con relación a la existência de mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The spherical model was the most adjusted one to the weed plants data, corroborating to other studies that describe this model as the most adjusted one with soil and plant data (Cambardella et al, 1994;Vieira, 2000;Chiba et al, 2010;Siqueira et al, 2015), excepting the Pure nugget effect diversity), with the exception of the total diversity that adjusted to the spherical model (Table 5). Several studies have reported that some weed species are aggregated or occur in reboilers, so the infestation mapping of the agricultural area enables located management application.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The spherical model was the most adjusted one to the weed plants data, corroborating to other studies that describe this model as the most adjusted one with soil and plant data (Cambardella et al, 1994;Vieira, 2000;Chiba et al, 2010;Siqueira et al, 2015), excepting the Pure nugget effect diversity), with the exception of the total diversity that adjusted to the spherical model (Table 5). Several studies have reported that some weed species are aggregated or occur in reboilers, so the infestation mapping of the agricultural area enables located management application.…”
Section: Resultssupporting
confidence: 87%
“…Siqueira et al (2015) studying the variability of weed found a range between 40 and 210 m. The spatial dependence reason was calculated according to Cambardella et al (1994), was high for Chamaesyce sp., E. indica, B. pilosa, Simpson (D), Simpson diversity and McIntosh Diversity (RD = 0.0 to 25%), medium for C. echinatus and Total diversity (RD = 25-75%).…”
Section: Resultsmentioning
confidence: 97%
“…In a given area, geostatistical techniques can identify properties that are treated as homogeneous but would need a differentiated management (Ribeiro et al, 2016). Moreover, by these techniques, soil properties can be understood, modelled, and mapped to identify specific management zones and reduce the effects of soil variability on crop yields (Siqueira et al, 2009;Chiba et al, 2010;Montanari et al, 2010;Carvalho et al, 2014;Zonta et al, 2014;Aquino et al, 2015;Montanari et al, 2015;Siqueira et al, 2015aSiqueira et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%